Prosantrimore sebagai Inovasi Pendidikan Islam di Era Digital: Integrasi Pesantren dalam Sekolah Negeri di SMA Negeri Glenmore - Zulma Qurrota Ainaya; Muhammad Husain (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to analyze the integrative model of pesantren-based education implemented through the Prosantrimore program at SMA Negeri Glenmore as an innovation in Islamic education within public schools in the digital era. The study employed a qualitative approach with a case study design to examine the processes of religious habituation, digital behavior management, and collaborative educational practices between schools and families. Data were collected through participant observation, in-depth interviews with the principal, program coordinators, teachers, and students, as well as documentation review. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the success of Prosantrimore is supported by three main components: systematic religious habituation, digital behavior control based on pesantren values, and collaborative management between teachers and parents. The program contributes not only to strengthening students’ religious character but also to developing ethical digital behavior and school culture management. This study contributes to the development of an integrative Islamic education model that combines character education, digital ethics, and collaborative educational management within public schools. The findings imply that pesantren-based educational integration can serve as an innovative strategy for strengthening character education policies in the digital era.